ANALISIS KONDISI SOSIAL EKONOMI MASYARAKAT PASCA TERJADINYA BENCANA GEMPA BUMI NAGARI MALAMPAH KECAMATAN TIGO NAGARI PASAMAN - Ropi Siska Putri; Erna Juita; Rika Despica (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to find out how the socio-economic conditions of the community are in terms of the aftermath of the earthquake in Nagari Malampah, Tigo Nagari District, Pasaman Regency. This type of research is quantitative research using proportional random sampling techniques. The sample for this research was the head of a family chosen randomly in each Jorong area that was affected by the earthquake, so the total number of samples in Nagari Malampah was 141 heads of families affected by the earthquake. From the results of research on the social conditions of the community after the earthquake in Nagari Malampah, Tigo Nagari District, Pasaman Regency, it can be concluded that the social conditions of the community in Nagari Malampah, Tigo Nagari District, Pasaman Regency amounted to (57.09%) based on the criteria in the Percentage table included in the category